In memory of Uttar Goran’s grammarian: the life and legacy of Shah Abdul Hannan - Hasan, Md. Mahmudul (2022)
Given the endemic venality that has gripped many societies, it is important to remember bureaucrats like Shah Abdul Hannan. His life serves as an example of honesty, integrity, and efficiency for our current and future generations. People like him are oases in a desert of mediocrity, sleaze, and hypocrisy. The country desperately needs people like him, with his consummate honesty, impeccable propriety, and unflinching courage.